Identity Negotiation and Gendered Communication Practices among Single-Mother Micro-Entrepreneurs in West Java: An Interpretative Phenomenological Analysis - Lina Karlina; Indra N.A Pamungkas (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study aims to analyze the negotiation of communication identity among single mothers who run micro-enterprises using the Communication Theory of Identity (CTI) framework. The research seeks to understand how identity is constructed across personal, enacted, relational, and communal layers, and how these interactions shape their gender performativity and business practices. The study contributes theoretically by positioning survival as a conceptual outcome of identity negotiation, extending the application of CTI within the context of marginalized women entrepreneurs. A qualitative approach was employed, utilizing in-depth interviews, observation, documentation, and data analysis through NVivo software to identify coding patterns and word similarities. The findings reveal that identity is formed dynamically through interconnected character traits, generating emergent attributes such as proactive, adaptive, accountable, integrity-driven, strategic, empathetic, realistic, credible, pragmatic, and ultimately survival-oriented. Survival emerges as the core identity strategy, not merely as economic endurance but as a communicative and performative process that integrates authenticity and pragmatism. This study highlights that single mothers’ empowerment lies in their ability to continuously negotiate identity across domestic and public spheres to sustain both family life and business continuity.